ANALYSIS OF THE MAIN DIRECTIONS OF GASTRONOMIC TOURISM IN THE CRIMEA - M. A. Boyarkina; I. A. Prokopenko (Современная наука и инновации, 2022)
This article analyzes the existing directions of gastronomic tourism on the Crimean Peninsula. The list of gastronomic locations in Crimea for 2019 is presented. The main problems of the development of gastronomic tourism on the Peninsula are identified.